2013
DOI: 10.1007/jhep01(2013)187
|View full text |Cite
|
Sign up to set email alerts
|

Naturalness of the non-universal MSSM in the light of the recent Higgs results

Abstract: We analyse the naturalness of the Minimal Supersymmetric Standard Model (MSSM) in the light of recent LHC results from the ATLAS and CMS experiments. We study nonuniversal boundary conditions for the scalar and the gaugino sector, with fixed relations between some of the soft breaking parameters, and find a significant reduction of finetuning for non-universal gaugino masses. For a Higgs mass of about 125 GeV, as observed recently, we find parameter regions with a fine-tuning of O (10), taking into account exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 91 publications
(150 reference statements)
2
28
0
Order By: Relevance
“…It has been observed that this can reduce the hierarchy problem through the appearance of a new "focus point" that makes the Higgs mass less sensitive to the gaugino mass scale [16][17][18][19][20][21][22][23][24][25][26]. Here we explore this possibility in detail for both the MSSM and GNMSSM in the context of the latest LHC bounds on SUSY states and the measurement of the Higgs mass.…”
Section: Jhep11(2013)209mentioning
confidence: 99%
“…It has been observed that this can reduce the hierarchy problem through the appearance of a new "focus point" that makes the Higgs mass less sensitive to the gaugino mass scale [16][17][18][19][20][21][22][23][24][25][26]. Here we explore this possibility in detail for both the MSSM and GNMSSM in the context of the latest LHC bounds on SUSY states and the measurement of the Higgs mass.…”
Section: Jhep11(2013)209mentioning
confidence: 99%
“…However, this also makes it very difficult to test even in the long run. A similar conclusion is shared in the context of gravity mediation by grand unified theory (GUT) models with the non-universal gaugino masses induced by the breaking of the GUT group [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 66%
“…1 the resulting ∆ EW for the points of our scan, as defined by Eqs. (13,14). The orange points correspond to the observed Higgs mass, once a theoretical uncertainty of 3 GeV is taken into account: 122 GeV ≤ m h ≤ 128 GeV.…”
Section: Models With Low Tuning and Typical Spectramentioning
confidence: 99%
“…The original focus point allowed to obtain the proper electroweak symmetry breaking scale for large values of the squark and slepton masses and subleading values of the stop mixing parameter A t and gaugino masses M a . More recently, this solution was reconsidered, including the presence of large stop mixing A t [11], large (non universal) gaugino masses [12][13][14] and in the framework of gauge mediation [15,16].…”
Section: Jhep04(2014)093mentioning
confidence: 99%